A novel function of RIP1 in postnatal development and immune homeostasis by protecting against RIP3-dependent necroptosis and FADD-mediated apoptosis - Dowling, John P.; Nair, Anirudh; Zhang, Jianke (Frontiers in Cell and Developmental Biology, 2015)
RIP1 is an adaptor kinase originally identified as being able to associate with TNFR1 and Fas, and is later shown to be involved in signaling induced by TLRs. Major signaling pathways regulated by RIP1 include necroptosis, apoptosis, and pro-survival/inflammation NF-B activation. Previous studies show that RIP1 deficiency has no effect on mouse embryogenesis, but blocks postnatal development. This phenotype could not readily be explained, since mice lacking TNFR1, Fas, or TLRs show no apparent developmental defect. Certain types of RIP1-deficient cells are hypersensitive to TNF-induced apoptosis. However, in our previous study, deletion of the apoptotic adaptor protein, FADD, provides marginal improvement of postnatal development of rip1-/- mice. Remarkably, the current data shows that haploid insufficiency of RIP3, a known mediator of necroptosis, allowed survival of rip1-/-fadd-/- mice beyond weaning age, although the resulting rip1-/-fadd-/- rip3+/- mice were significant smaller in size and weight. Moreover, complete absence of RIP3 further improved postnatal development of the resulting rip1-/-fadd-/-rip3-/- mice, which display normal size and weight. In such triple knockout (TKO) mice, lymphocytes underwent normal development, but progressively accumulated as mice age. This lymphoproliferative (lpr) disease in TKO mice is, however, less severe than that of fadd-/-rip3-/- double knockout mice. In total, the data show that the postnatal developmental defect in rip1-/- mice is due in part to FADD-mediated apoptosis as well as RIP3-dependent necroptosis. Moreover, the function of RIP1 contributes to development of lpr diseases.